Political Branding : Content Analysis Of Debate Of Candidates For Vice Governor Of East Java Session I In Poverty Reduction - Pratama, Bayu Indra; Ilahi, Azizun Kurnia; Amalia Avina, Diyah Ayu (KOMUNIKA, 2022)
This study aims to understand how the Political branding strategy developed by the Candidates for Governor and Vice governor with regard to poverty alleviation in the East Java region. This "political battle" becomes interesting because each pair of Khofifah and Emil or Saifullah Yusuf and Puti Guntur Soekarno are not new figures in the East Java political arena. The background and political capital of each partner seems to be at stake because of the long and deep history and closeness to East Java. In the context of the issue of poverty, it becomes important how they conduct public debates in order to do  maneuver to overcome this classic problem and all parties agree that poverty must be fought. This study uses content analysis from the first session of the open debate on the Candidates for Governor and Vice governor of East Java. In the end, this study shows the superiority of the Khofifah and Emil Dardak in discussing the issue of poverty, but the Saifullah Yusuf and Puti Guntur Soekarno also have their own characteristics in discussing the issue of poverty. Each has its own political branding focus and strategy in conveying their ideas.